Growth, Productivity And Soil Health In Wheat (Triticum Aestivum L.) As Influenced By Organic And Inorganic Fertilizers (International Journal of Environmental Sciences, 2025)
A field experiment entitled “Growth, productivity and soil health in wheat (Triticum aestivum L.) as influenced by organic and inorganic fertilizers” was conducted during rabi season of 2024-25 at Research Farm, Guru Kashi University, Talwandi Sabo, Bathinda (Punjab). The experiment was conducted in Randomized Complete Block Design (RCBD) with one control and 7 treatments with three replications. The treatments consisted of T1: Control (No fertilizer), T2: Recommended dose of fertilizer (RDF) {125 N: 62.5 P2O5: 30 K2O kg ha-1}, T3: 50% RDF + Vermicompost @ 2 t/ha, T4: 75% RDF + Vermicompost @ 2 t/ha, T5: 50% RDF + Farmyard manure (FYM) @ 5 t/ha, T6: 75% RDF + Farmyard manure (FYM) @ 5 t/ha, T7: Vermicompost @ 5 t/ha, T8: Farmyard manure (FYM) @ 10 t/ha. Results showed that recommended dose of fertilizer (RDF) and 75% RDF + Farmyard manure (FYM) @ 5 t/ha (T6) resulted in statistically similar growth parameters viz., plant height, leaf area index, number of tillers and yield attributes viz., number of effective tillers, number of grains/ear and 1000-grain weight in wheat. Treatment recommended dose of fertilizer (T2) recorded significantly higher grain and straw yield of wheat than other fertilizer treatments, however, it was statistically at par with 75% RDF + Farmyard manure @ 5 t/ha. (T6). The increase in grain yield with RDF was 42.9, 18.5, 13.5, 5.6, 3.4, 31.8 and 25.4% than the T1, T3, T4, T5, T6, T7 and T8, respectively. Farmyard manure (FYM) @ 10 t/ha alone and with RDF significantly improved the soil organic carbon, available nitrogen, phosphorous and potassium in soil than control.